La gestión financiera y su relación con la toma de decisiones en la empresa AF Boullosa De Iquitos, periodo 2023 - Vigo Valderrama, Milagros (2023)
Financial management includes a series of actions and procedures that are linked to adequate administration and control of a company's finances, which must be aimed at being used appropriately to achieve the objectives and goals of the organization, being Thus, management will be able to make correct decisions that will result in an increase in economic and profitable benefits. The research is called “Financial Management and its relationship with decision-making in the AF Boullosa company of Iquitos, period 2023”, its objective is to determine the relationship between financial management and decision-making in the indicated period. The study was quantitative and correlational descriptive design, the survey was used as a technique and the questionnaire as an instrument to collect data, it was applied in a sample made up of 35 workers. Finally, after processing and analyzing the information through the spss v25 statistical software, a Spearman's Rho correlation coefficient of 0.291 and a degree of significance of 0.001 and 0.000 were obtained, indicating a low correlation.